Creativity and semantic processing in the brain : an MEG study of N400 - Lehikoinen, Iina (2020)
Creativity is an ability that has a fundamental status in defining human nature. The processes and components of creativity have long been considered mystical and unresearchable, but contemporary studies permit the examination of creative abilities like any other cognitive process. This study examined possible links between creativity and semantic processing in the brain, indicated by N400 event-related potential. Participants (n=8) were university students, aged between 19 and 25. Brain activation was measured with magnetoencephalography (MEG) during a three-word list task, in which half of the lists were congruent (all items semantically related to each other) and half were incongruent (first two words were related, but the last word broke the pattern). Creativity was measured with self-assessment of creative abilities (K-DOCS), Design Fluency Test, and a questionnaire about creative hobbies. Cognitive skills were assessed with parts of Wechsler Adult Intelligence Scale (WAIS). The proposed hypothesis was based on theory about creativity as ease of association. It was assumed that higher creativity is associated with easier semantic association, and hence correlates with more effortless semantic categorization. This was hypothesised to manifest as a smaller semantic N400 effect. Results showed that the presented stimuli created an expected N400 effect; a greater N400 amplitude was seen for incongruent stimuli than to congruent. Self-assessed creativity (average creativity and performance-related creativity) correlated positively with the magnitude of semantic effect in the left hemisphere. On the other hand, hobbies related to music production, Design Fluency Test scores and working memory (WAIS) correlated positively with the semantic effect magnitude in the right hemisphere. Direction of correlations was opposite to what was assumed by the hypothesis: greater scores on creativity tests correlated with greater semantic effect. Hence, more creative people exhibit a larger N400 effect. However, it is possible that more creative people actually require more effort in semantic processing, because they possess a larger semantic network. This study was executed with a small number of participants, and more research is needed to uncover the processes that underlie creativity and how it might be connected to semantic processing.